2009
DOI: 10.21897/rmvz.362
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidad Ileal Aparente De La Proteina Y Aminoácidos De La Torta De Canola en Lechones Recién Destetados

Abstract: RESUMENObjetivo. Obtener los coeficientes de digestibilidad ileal aparente (CDIA) de proteína (PC) y aminoácidos (AA) de torta de canola, en lechones recién destetados. Materiales y métodos. Se utilizaron 24 lechones destetados a los 17 días de edad con un peso de 5.5 kg, a los cuales se les fijó una cánula simple en "T" en el ileon distal. Los lechones recibieron uno de los siguientes tratamientos: Dieta de Referencia (C) elaborada con caseína y almidón de maíz; dietas CTC (caseína-10% de Torta de canola) y C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…Moreover, the smaller values for the AIDC of protein and amino acids of CM seen in this study were similar to those reported by Mariscal et al (2009) who reported low AIDC for most amino acids, ranging from 40% to 60%. The reduction in digestibility coefficients of protein and amino acids can be attributed to the high levels of fiber contained in CM compared to other, more digestible protein sources (MINKOWSKI, 2002).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the smaller values for the AIDC of protein and amino acids of CM seen in this study were similar to those reported by Mariscal et al (2009) who reported low AIDC for most amino acids, ranging from 40% to 60%. The reduction in digestibility coefficients of protein and amino acids can be attributed to the high levels of fiber contained in CM compared to other, more digestible protein sources (MINKOWSKI, 2002).…”
Section: Resultssupporting
confidence: 91%
“…The low digestibility of threonine may be partly due to its low rate of absorption in the small intestine (MARISCAL et al, 2009). Furthermore, according to Fan et al (1995), based on the specificity of the endogenous proteases and peptidases, threonine is the last amino acid to be released by enzymatic hydrolysis of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The AID of amino acids, energy, and phosphorus was calculated using the following equation: AID = [1 − [(TiD × NI)/(ND × TiI)] × 100 where TiD is the concentration of TiO 2 in the diet; NI is the concentration of the nutrient in the ileal digesta; ND is the concentration of the nutrient in the diet; and TiI is the concentration of TiO 2 in the ileal digesta [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ahmed et al (7) determined the actual and apparent digestibility of extruded canola flour and concluded that extrusion improves apparent digestibility of raw protein, amino acids, raw energy and energy that can be metabolized. Therefore, Mariscal et al (8) en forma extrusada o peletizada pueden ser utilizados en la sustitución parcial de la harina de soya. Ahmed et al (7) determinaron la digestibilidad real y aparente de la harina de canola extrusada y concluyeron que la extrusión mejora la digestibilidad aparente de la proteína cruda, aminoácidos, energía bruta y energía metabolizable, entre tanto, Mariscal et al (8) determinaron los coeficientes de digestibilidad real aparente y estandarizada de la proteína y aminoácidos de la torta de canola peletizada en lechones recién destetados.…”
Section: Introductionunclassified
“…Therefore, Mariscal et al (8) en forma extrusada o peletizada pueden ser utilizados en la sustitución parcial de la harina de soya. Ahmed et al (7) determinaron la digestibilidad real y aparente de la harina de canola extrusada y concluyeron que la extrusión mejora la digestibilidad aparente de la proteína cruda, aminoácidos, energía bruta y energía metabolizable, entre tanto, Mariscal et al (8) determinaron los coeficientes de digestibilidad real aparente y estandarizada de la proteína y aminoácidos de la torta de canola peletizada en lechones recién destetados. Ellos concluyeron que el proceso de peletización mejora la digestibilidad real de la proteína y de los aminoácidos.…”
Section: Introductionunclassified